Coastal Community Empowerment by Mitra Bentala Indonesia and Academics in Formation Waste Bank Group in Kota Karang Subdistrict (Baskora): Pemberdayaan Masyarakat Pesisir oleh Mitra Bentala Indonesia dan Akademisi dalam Pembentukan Kelompok Bank Sampah di Kelurahan Kota Karang (Baskora) - Lestari, Sepnina Like; Rizani; Ajitio, Ogja; Patria, Yoga; Mashabi; Mayaguezz, Henky; Febryano, Indra Gumay (Prosiding Seminar Nasional Ilmu Teknik Dan Aplikasi Industri Fakultas Teknik Universitas Lampung, 2025)
The waste problem in the coastal areas of Bandar Lampung City is a complex environmental challenge, primarily due to the high volume of household waste and limited management systems. This study aims to analyze the co-creation model in empowering coastal communities through the establishment and operation of the BASKORA Waste Bank in Kota Karang Village, Bandar Lampung. The approach used was descriptive qualitative supported by quantitative data, including field observations, interviews, and waste volume analysis during seven weeks of activity. The results showed that community participation increased significantly, from 11 customers in the first week to 40 customers in the seventh week, with a total of 624.1 kg of managed waste. The dominant types of waste included plastic bottles and cups (144.1 kg), hard plastic (91.36 kg), and mixed/other (94.6 kg), indicating public awareness of the economic value of high-value waste. The increase in the volume and frequency of waste deposits showed a positive correlation between community participation and the effectiveness of mentoring. Conceptually, BASKORA demonstrates that collaboration between communities, academics, and non-governmental organizations through co-creation mechanisms can transform ecological behavior while creating a circular economic system at the local level. Therefore, this model can be replicated in other coastal areas as an empowerment strategy that integrates social, economic, and environmental sustainability aspects.